Tính minh bạch thương hiệu và hành vi mua sản phẩm bền vững: Góc nhìn từ động lực xanh và giá trị cảm xúc - Dinh Van, Hoang; Vu Thi Thuy, Linh; Le Anh, Quan; Nguyen Nang Thuy, Nguyen (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines the influence of brand transparency on consumers’ intention to purchase sustainable products, and also clarifies the mediating role of green extrinsic motivation and emotional value. The study employs a quantitative method through a consumer survey, with 357 valid samples analyzed by partial least squares structural equation modeling (PLS-SEM). The results show that brand transparency positively influences sustainable product purchase intention, green extrinsic motivation, and emotional value. Furthermore, green extrinsic motivation plays a mediating role in this relationship, while emotional value does not demonstrate a statistically significant mediating effect. The study also confirms the positive influence of green extrinsic motivation and emotional value on sustainable product purchase intention, and shows the positive influence of emotional value on green extrinsic motivation.. The research results contribute to both the theory of sustainable consumer behavior and corporate governance practice.